2012
DOI: 10.1111/j.1540-6210.2012.02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and Government Contracting: Different Explanations or New Prospects for Theory?

Abstract: The U.S. Congress created the Small Disadvantaged Business (SDB) and Women‐Owned Small Business (WOSB) programs to promote fairness in government contracting. In this article, the authors examine whether increases in racial and gender representation in federal agencies correlate with the proportion of contract dollars awarded to women‐ and minority‐owned firms. Using the theory of representative bureaucracy as a starting point, they find evidence that increases in passive minority representation result in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Also in the area of education, Nicholson-Crotty, Grissom, and Nicholson-Crotty ( 2011 ) find that black teachers are more likely to refer black students to gifted and talented programs than their white counterparts (see also Grissom, Nicholson-Crotty, and Nicholson-Crotty 2009 ). In the U.S. federal procurement arena, Fernandez, Malatesta, and Smith ( 2013 ) find that increasing racial minority representation enables agencies to become more effective at achieving the legislatively mandated goal of promoting minorityowned small business participating in federal contracting. And Selden ( 1997 ) finds that an increase in the percentage of administrators in the U.S. Department of Agriculture ' s Farmers Home Administration who were black, Hispanic, and Asian American led to an increase in the number of loan eligibility awards favoring black, Hispanic, and Asian American loan applicants, respectively.…”
Section: The Theory Of Representative Bureaucracymentioning
confidence: 99%
“…Also in the area of education, Nicholson-Crotty, Grissom, and Nicholson-Crotty ( 2011 ) find that black teachers are more likely to refer black students to gifted and talented programs than their white counterparts (see also Grissom, Nicholson-Crotty, and Nicholson-Crotty 2009 ). In the U.S. federal procurement arena, Fernandez, Malatesta, and Smith ( 2013 ) find that increasing racial minority representation enables agencies to become more effective at achieving the legislatively mandated goal of promoting minorityowned small business participating in federal contracting. And Selden ( 1997 ) finds that an increase in the percentage of administrators in the U.S. Department of Agriculture ' s Farmers Home Administration who were black, Hispanic, and Asian American led to an increase in the number of loan eligibility awards favoring black, Hispanic, and Asian American loan applicants, respectively.…”
Section: The Theory Of Representative Bureaucracymentioning
confidence: 99%
“…From a relational demography perspective, individuals tend to react more positively to those with shared demographic characteristics, which might influence recruitment, career advancement, and compensation (Cohen, Broschak, and Haveman 1998 ;Grissom, Nicholson-Crotty, and Keiser 2012 ). Studies on representative bureaucracy have found strong support for the passive-active link in terms of race (Hicklin and Meier 2008 ;Nicholson-Crotty, Grissom, and Nicholson-Crotty 2011 ;Pitts 2009 ;Selden 1997 ), but research on the effect of gender thus far has yielded mixed results (Fernandez, Malatesta, and Smith 2013 ;Meier and Nicholson-Crotty 2006 ;Selden 1997 ;Wilkins and Keiser 2006 ).…”
Section: Politics Representation and Improved Outcomes For Womenmentioning
confidence: 99%
“…In thinking about why the relationship between representation and outcomes associated with gender is less robust than for outcomes associated with race, some have identified intersectionality as a leading reason why women ' s passive representation does not always lead to active representation. Intersectionality is the notion that individuals have multiple identity categories (e.g., gender, race, age, sexual orientation) (Jackson and Ruderman 1995 ), and policy saliency determines whether a particular identity becomes dominant over other identities for an individual at a given time (Fernandez, Malatesta, and Smith 2013 ;Gay and Tate 1998 ). For example, Gay and Tate ( 1998 ) analyze survey data on black women ' s political attitudes and identify race as the stronger predictor of their attitudes compared with gender.…”
Section: Politics Representation and Improved Outcomes For Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is a clustering of topics within some subareas. For example, within budgeting and financial management, the articles related to social equity are primarily focused on minority contracting and set‐asides (see, e.g., Fernandez, Malatesta, and Smith ; Martin, Berner, and Bluestein ; Rice ; Smith and Fernandez ). Table provides example PAR social equity publications by subarea.…”
Section: Milestones On the Social Equity Timelinementioning
confidence: 99%